A historiografia como problema : Nietzsche e a história magistra vitae, a história científica e a história genealógica e afirmadora da vida - Raylane Marques Sousa (2016)
In this thesis, we examine the thinking of Friedrich W. Nietzsche concerning history in the 19th century. The interest of Nietzsche for history is central in his whole philosophical project and the relationship he establishes with the historical knowledge is often misunderstood, sometimes because of his moving and unsystematic thinking. Therefore, our first objective is to examine the hypothesis according to which Nietzsche would be a thinker who is situated between the magistra vitae history and the science history, but who returns strategically to the moralizing history model of the ancients with the intention of devaluing the scientific history model of the moderns and, from then on, proposing a new history model, of the genealogical type and affirmer of life. Once that is done, our second objective in this research is to analyze the assumption that that new model of history of Nietzsche brings together both elements of the magistra vitae history and elements of the science history, being at the same time beyond the old and modern models of history (Historie / Geschichte). At the end of our work, we intend to place Nietzsche as an untimely philosopher, that is, as a thinker that fights against his own time to make his new model of history start to guide the practical life. We aim at demonstrating the plausibility of these hypotheses, taking as reference mainly the following works of Nietzsche: Untimely Meditations II: On the Uses and Disadvantages of History for Life (1874) and On the Genealogy of Morality (1887). Other works from the youth as well as the intermediate and maturity periods of Nietzsche are also fundamental to support these hypotheses, such as: On the Future of our Educational Institutions (1872), On Truth and Lies in a Nonmoral Sense (1873), Untimely Meditations I: David Strauss, the Confessor and the Writer (1873), Untimely Meditations III: Schopenhauer as Educator (1874), Aurora (1881), The Gay Science (1882), Beyond Good and Evil (1886), The Antichrist (1888) and Ecce Homo (1888).